2012
DOI: 10.1111/j.1365-2672.2012.05437.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosusvar.plantarumC29 protects scopolamine-induced memory deficit in mice

Abstract: Aims: In the preliminary study, kimchi, a traditional food fermented with Chinese cabbage, protected scopolamine-induced mouse memory deficit in passive avoidance test. Therefore, we screened protective ingredients, particularly lactic acid bacteria, from Chinese cabbage kimchi against scopolamine-induced memory deficit in mice. Methods and Results: Lactic acid bacteria, isolated from Chinese cabbage kimchi, were identified by 16S rDNA sequence analysis, G+C content and cellular fatty acid composition and suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…Recent studies have found that the L. plantarum versus pentosus showed a protective effect against memory deficit in AD-induced mice by D-Galactose and scopolamine [12,18]. Further, another study reported that L. Plantarum NDC75017 improves the learning and memory ability in aging rats [19].…”
Section: Lactic Acid Bacteria (Probiotics) and D-galactose Induced Almentioning
confidence: 98%
“…Recent studies have found that the L. plantarum versus pentosus showed a protective effect against memory deficit in AD-induced mice by D-Galactose and scopolamine [12,18]. Further, another study reported that L. Plantarum NDC75017 improves the learning and memory ability in aging rats [19].…”
Section: Lactic Acid Bacteria (Probiotics) and D-galactose Induced Almentioning
confidence: 98%
“…Acquisition and retention of the passive avoidance task was conducted using a two-compartment acrylic box wherein a lighted compartment (20 cm  20 cm  20 cm) was connected to a dark compartment (20 cm  20 cm  20 cm) by an entrance door (5 cm  5 cm), like previously reported (Jung et al, 2013). Memory impairment was induced by the intraperitoneal injection of scopolamine (1 mg/kg) 30 min after the oral administrations of test agents.…”
Section: Animal Studymentioning
confidence: 99%
“…The number of arm entries was served as the indicator of locomotor activity. The Morris water maze task was performed, like the previously reported (Jung et al, 2013). Test agents [SE (100 mg/kg), FSE (100 mg/kg), tacrine (10 mg/kg) and vehicle (2% Tween-80, the scopolamine group)] were administered orally into mice 1 h before test was performed at every consecutive day.…”
Section: Animal Studymentioning
confidence: 99%
See 2 more Smart Citations